Analisis Pengungkapan Sukarela pada Bank Umum Syariah di Indonesia - Muhammad Haidir Ali; Ahmad Tarmidzi Lubis (Jurnal Akuntansi dan Keuangan Islam, 2015)
This study is a descriptive study to assess voluntary disclosure in annual reportsIslamic Banks (iB) with that should be disclosed. Annual reports used in this study isan annual report iB in Indonesia in 2011, 2012, and 2013. This research is relativelynew because no one has done research on voluntary disclosure in Islamic Banks (iB).Therefore, in order to study to obtain maximum results, the coding instructions forvoluntary disclosure must be in accordance with the study conducted by Rr. PuruwitaWardani (2012) entitled "Factors Affecting Voluntary Disclosure area. Analysis toolsare used is the content analysis by collecting words that expressed the count. Theresults showed that during the three-year study period, 2011, 2012, and 2013 therewas an increase in the provision of good disclosure of the number of items disclosedor revealed iB number. But overall tenth iB already provide adequate voluntarydisclosure to reveal the items contained in the variable voluntary disclosure eventhough the iB newly established in 2010.